Curcumin and its derivatives in cancer therapy: Potentiating antitumor activity of cisplatin and reducing side effects. (25th October 2021) - Abadi, Asal Jalal; Mirzaei, Sepideh; Mahabady, Mahmood Khaksary; Hashemi, Farid; Zabolian, Amirhossein; Hashemi, Fardin; Raee, Pourya; Aghamiri, Shahin; Ashrafizadeh, Milad; Aref, Amir Reza; Hamblin, Michael R.; Hushmandi, Kiavash; et al.
Abstract: Curcumin is a phytochemical isolated from Curcuma longa with potent tumor‐suppressor activity, which has shown significant efficacy in pre‐clinical and clinical studies. Curcumin stimulates cell death, triggers cycle arrest, and suppresses oncogenic pathways, thereby suppressing cancer progression. Cisplatin (CP) stimulates DNA damage and apoptosis in cancer chemotherapy. However, CP has adverse effects on several organs of the body, and drug resistance is frequently observed. The purpose of the present review is to show the function of curcumin in decreasing CP's adverse impacts and improving its antitumor activity. Curcumin administration reduces ROS levels to prevent apoptosis in normal cells. Furthermore, curcumin can inhibit inflammation via down‐regulation of NF‐κB to maintain the normal function of organs. Curcumin and its nanoformulations can reduce the hepatoxicity, neurotoxicity, renal toxicity, ototoxicity, and cardiotoxicity caused by CP. Notably, curcumin potentiates CP cytotoxicity via mediating cell death and cycle arrest. Besides, curcumin suppresses the STAT3 and NF‐ĸB as tumor‐promoting pathways, to enhance CP sensitivity and prevent drug resistance. The targeted delivery of curcumin and CP to tumor cells can be mediated nanostructures. In addition, curcumin derivatives are also able to reduce CP‐mediated side effects, and increase CP cytotoxicity against various cancer types.